2013
DOI: 10.3174/ajnr.a3373
|View full text |Cite
|
Sign up to set email alerts
|

3D Computational Fluid Dynamics of a Treated Vertebrobasilar Giant Aneurysm: A Multistage Analysis

Abstract: BACKGROUND AND PURPOSE:The treatment of giant aneurysms of the vertebrobasilar junction remains a challenging task in neurosurgical practice, and the reference standard therapy is still under debate. Through a detailed postmortem study, we analyzed the hemodynamic factors underlying the formation and recanalization of an aneurysm located at this particular site and its anatomic configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…VETMs can be used to pre‐operatively predict the likelihood of recanalization in candidate aneurysms for coil embolization. Presence of high WSS (>35 Pa as reported by Refs ) at the neck of the coiled aneurysms was shown to have a correlation with post‐treatment recanalization and regions of high WSS coincided with regions where recanalization happened …”
Section: Modeling Of Endovascular Devices and Their Deploymentsupporting
confidence: 61%
See 1 more Smart Citation
“…VETMs can be used to pre‐operatively predict the likelihood of recanalization in candidate aneurysms for coil embolization. Presence of high WSS (>35 Pa as reported by Refs ) at the neck of the coiled aneurysms was shown to have a correlation with post‐treatment recanalization and regions of high WSS coincided with regions where recanalization happened …”
Section: Modeling Of Endovascular Devices and Their Deploymentsupporting
confidence: 61%
“…Presence of high WSS (>35 Pa as reported by Refs 155,156) at the neck of the coiled aneurysms was shown to have a correlation with post-treatment recanalization and regions of high WSS coincided with regions where recanalization happened. [155][156][157][158] Delayed or incomplete occlusion and posttreatment rupture are the challenging complications associated with flow diverter treatments. Currently, there is no reliable measure to predict the performance of implanted flow diverters in terms of inducing a durable clot that occludes the sac completely and triggers the process of healing.…”
Section: Modeling Of Endovascular Devices and Their Deploymentmentioning
confidence: 99%
“…Additionally, they suggest that bleb formation can be the result of a high-WSS induced pathological pathway. Similarly, all available literature 10,[46][47][48][49] (in our knowledge) associate recanalization of the treated aneurysm with the occurrence of high-WSS patch at the neck. So for the present study, we treat an increase in WSS after foam insertion as a risk factor.…”
Section: Discussionmentioning
confidence: 68%
“…These are typically the areas where focal fusiform dilatations occur in VBDAs. In a case report examining hemodynamic characteristics of a giant vertebrobasilar junction aneurysm, Graziano et al found high velocity of blood flow at the aneurysm neck with stagnant, low flow conditions in the central portion of the aneurysm 20. In another case report, Hassan et al reported CFD findings in a patient with a giant fusiform vertebrobasilar aneurysm and found complex intra-aneurysmal flow patterns with vortex type flow in an area of thrombosis 21.…”
Section: Discussionmentioning
confidence: 99%